Evaluation of celiac disease with uniphasic and multiphasic dynamic MDCT imaging. - Göya, Cemil; Dündar, İlyas; Özgökçe, Mesut; Türkoğlu, Saim; Türko, Ensar; Özkaçmaz, Sercan; Aydoğdu, Gülay; Almalı, Necat (Abdominal Radiology, 2021)
Purpose: An analysis of dynamic contrast MRI has been shown to provide valuable information about disease activity in Crohn's disease and Celiac disease (CD). However, there are no reports of dynamic multi-detector computer tomography use in patients with CD. The aim of this study is to determine and compare the perfusion dynamics of the patients treated with control subjects and the perfusion dynamics in patients with untreated CD, using dynamic contrast in MDCT and compare studying contrast dynamics in Marsh types as well. Methods: In this retrospective study, uniphasic and multiphasic MDCT, untreated, treated, incompatible CD patients and healthy control group duodenum wall thickness and HU values were compared in terms of patient groups and modified Marsh types. Result: In dynamic CT, the highest contrast curve was observed in the untreated group and Marsh type 1. While the contrast curve of the untreated and non-compliant patients increased rapidly and showed wash out, the type 4 contrast curve was observed, whereas the treated and control group slowly increased type 5 contrast curve. In the contrast-enhanced CT in the venous phase, in the ROC analysis between Marsh 1–2 and Marsh 3a–c, the sensitivity was 97% and the specificity was 87% when the cut off was taken as 4.45 mm for wall thickness (p: 0.005). Conclusion: Contrast-enhanced single-phase and dynamic MDCT imaging in CD patients may be useful in evaluating the inflammatory and pathological process in the small intestine.